Two-stage seedling cultivation method for sweet peppers combining closed plant factory and solar greenhouse - Cui, Hongbo; Ji, Fang; Luo, Zhengyang; Wang, Xiufeng; Wang, Jianfeng (International Journal of Agricultural and Biological Engineering, 2024)
This study introduced a two-stage cultivation method for sweet pepper seedlings, integrating the strengths of a closed plant factory and solar greenhouse, to mitigate the environmental constraints in Northeast China during the early spring season. In the first stage, seedlings were cultivated in a closed plant factory, followed by a second stage in a solar greenhouse. Four treatments- T1 (9 and 36 d), T2 (12 and 33 d), T3 (15 and 30 d), and T4 (18 and 27 d) - were designed for the first and second stages, respectively, with solar greenhouse-only approach serving as the control (CK). The findings reveal that the two-stage methodology significantly outperformed the control across multiple metrics, including seedling health index, chlorophyll content, photosynthetic capacity, yield, etc. Specifically, T3 emerged as optimal, boosting the health index by 38.59%, elevating chlorophyll content by 39.61%, increasing net photosynthesis by 34.61%, and augmenting yield per plant by 40.67%. Additionally, T3 expedited the time to harvest by 25 d compared to the control. Although the seedling cost for T3 was 0.12 RMB yuan higher, the benefits offset the additional investment. In conclusion, the two-stage cultivation method effectively leverages the advantages of both closed-plant factories and solar greenhouses, resulting in superior seedling quality compared to using only solar greenhouses. It offers a practical and economically viable solution for enhancing the quality and yield of sweet pepper seedlings, thus contributing to the progress in the field of facility seedling cultivation research.Keywords: two-stage, seedling cultivation, sweet peppers, closed plant factory, solar greenhouseDOI: 10.25165/j.ijabe.20131606.8293Citation: Cui H B, Ji F, Liu Y N, Luo Z Y, Wang X F, Wang J F. Two-stage seedling cultivation method for sweet peppers combining closed plant factory and solar greenhouse. Int J Agric & Biol Eng, 2023; 16(6): 56–66.